Modeling of carbon pellets disruption mitigation in an NSTX-U plasma. (4th October 2021) - Clauser, C.F.; Jardin, S.C.; Raman, R.; Lyons, B.C.; Ferraro, N.M.
Abstract: Single carbon pellet disruption mitigation simulations using M3D- C 1 were conducted for an NSTX-U-like plasma to support the electromagnetic pellet injection concept. A carbon ablation model has been implemented in M3D- C 1 and tested with available data. 2D simulations were conducted in order to estimate the amount of carbon needed to quench the plasma, finding that the content in a 1 mm radius vitreous carbon pellet (∼3.2 × 10 20 atoms) would be enough if it is entirely ablated. 3D simulations were performed, scanning over pellet velocity and parallel thermal conductivity, as well as different injection directions and pellet concepts (solid pellets and shell pellets). The sensitivity of the thermal quench and other related quantities to these parameters has been evaluated. A 1 mm radius solid pellet only partially ablates at velocities of 300 m s −1 or higher, thus being unable to fully quench the plasma. To further enhance the ablation, approximations to an array of pellets and the shell pellet concept were also explored. 3D field line stochastization plays an important role in both quenching the center of the plasma and in heat flux losses, thus lowering the amount of carbon needed to mitigate the plasma when compared to the 2D case. This study constitutes an important step forward in 'predict-first' simulations for disruption mitigation in NSTX-U and other devices, such as ITER.